Modelling mountain pine beetle-impacted forest wildland fire fuel distributions from remotely piloted aircraft systems imagery and point clouds - Saeid Parsian; Christopher Hopkinson; Craig Coburn; Christopher Watson; Laura Chasmer (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Warmer air temperatures predicted to result in wetland drying in the Upper Columbia River Valley, British Columbia, Canada - Italo Sampaio Rodrigues; Christopher Hopkinson; Laura Chasmer; Ryan J. MacDonald; Suzanne E. Bayley (Science of The Total Environment, 2025)

Connectivity of evapotranspiration processes in a Brazilian dryland reservoir using remote sensing - Italo Sampaio Rodrigues; Gláuber Pontes Rodrigues; Carlos Alexandre Gomes Costa; Christopher Hopkinson; José Carlos de Araújo (Agricultural and Forest Meteorology, 2024)

Shortening fire return interval predisposes west‐central Canadian boreal peatlands to more rapid vegetation growth and transition to forest cover - Emily Ann Jones; Laura Elizabeth Chasmer; Kevin John Devito; Christopher Dennis Hopkinson (Global Change Biology, 2024)
Climate change in northern latitudes is increasing the vulnerability of peatlands and the riparian transition zones between peatlands and upland forests (referred to as ecotones) to greater frequency of wildland fires. We examined early post‐fire vegetation regeneration following the 2011 Utikuma complex fire (central Alberta, Canada). This study examined 779 peatlands and adjacent ecotones, covering an area of ~182 km 2 . Based on the known regional fire history, peatlands that burned in 2011 were stratified into either long return interval (LRI) fire regimes of >80 years (i.e., no recorded prior fire history) or short fire return interval (SRI) of 55 years (i.e., within the boundary of a documented severe fire in 1956). Data from six multitemporal airborne lidar surveys were used to quantify trajectories of vegetation change for 8 years prior to and 8 years following the 2011 fire. To date, no studies have quantified the impacts of post‐fire regeneration following short versus long return interval fires across this broad range of peatlands with variable environmental and post‐fire successional trajectories. We found that SRI peatlands demonstrated more rapid vascular and shrub growth rates, especially in peatland centers, than LRI peatlands. Bogs and fens burned in 1956, and with little vascular vegetation (classified as “open peatlands”) prior to the 2011 fire, experienced the greatest changes. These peatlands tended to transition to vascular/shrub forms following the SRI fire, while open LRI peatlands were not significantly different from pre‐fire conditions. The results of this study suggest the emergence of a positive feedback, where areas experiencing SRI fires in southern boreal peatlands are expected to transition to forested vegetation forms. Along fen edges and within bog centers, SRI fires are expected to reduce local peatland groundwater moisture‐holding capacity and promote favorable conditions for increased fire frequency and severity in the future.

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Iron limitation across chlorophyll gradients in the southern Drake Passage: Phytoplankton responses to iron addition and photosynthetic indicators of iron stress - Brian M. Hopkinson; B. Greg Mitchell; Rick A. Reynolds; Haili Wang; Karen E. Selph; Christopher I. Measures; Christopher D. Hewes; Osmund Holm-Hansen; Katherine A. Barbeau (Limnology and Oceanography, 2007)
Processes influencing phytoplankton bloom development in the southern Drake Passage were studied using shipboard iron‐enrichment incubations conducted across a surface chlorophyll gradient near the Antarctic Peninsula, in a region of water mass mixing. Iron incubation assays showed that Antarctic Circumpolar Current (ACC) waters were severely iron limited, while shelf waters with high ambient iron concentrations (1–2 nmol L −1 ) were iron replete, demonstrating that mixing of the two water masses is a plausible mechanism for generation of the high phytoplankton biomass observed downstream of the Antarctic Peninsula. In downstream highchlorophyll mixed waters, phytoplankton growth rates were also iron limited, although responses to iron addition were generally more moderate as compared to ACC waters. Synthesizing results from all experiments, significant correlations were found between the initial measurements of Photosystem II (PSII) parameters ( F v :F m , σ PSII , and p ) and the subsequent responses of these waters to iron addition. These correlations indicate that PSII parameters can be used to assess the degree of iron stress experienced in these waters and likely in other regions where photoinhibition and nitrogen stress are not confounding factors.